2021
DOI: 10.1002/jmv.27271
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical outcomes in renal transplant recipients with COVID‐19

Abstract: The coronavirus disease 2019 (COVID‐19) has affected more than a hundred million individuals and caused more than three million deaths worldwide. Specific risk groups were defined for increased risk of mortality and morbidity in COVID‐19, and renal transplant recipients are at a significantly increased risk regarding outcomes due to their immunosuppressed conditions. This study evaluated the general characteristics of kidney transplant recipients with COVID‐19 infection. Among 1257 transplant cases, 56 had COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A meta-analysis from Belsky et al, reviewed the disease course of immunodeficient patients infected by SARS-CoV-2 and found that solid organ transplant patients, who suffer from multiple comorbidities, are more likely to require intensive care, which is a surrogate for mortality 4 . E.g., in our cohort 7 patients with previous kidney transplantation had a mortality rate of 28.6%, in accordance to our results, Alberici et al, Yilmaz et al and Akalin et al found mortality rates of 28%, 23% and 25% in kidney transplant recipients with COVID-19 [29][30][31] . However, the mortality rate in our cohort was lower than in LEOSS patients with prior renal transplantation and CP therapy (45.5%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A meta-analysis from Belsky et al, reviewed the disease course of immunodeficient patients infected by SARS-CoV-2 and found that solid organ transplant patients, who suffer from multiple comorbidities, are more likely to require intensive care, which is a surrogate for mortality 4 . E.g., in our cohort 7 patients with previous kidney transplantation had a mortality rate of 28.6%, in accordance to our results, Alberici et al, Yilmaz et al and Akalin et al found mortality rates of 28%, 23% and 25% in kidney transplant recipients with COVID-19 [29][30][31] . However, the mortality rate in our cohort was lower than in LEOSS patients with prior renal transplantation and CP therapy (45.5%).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, a compromised immune response to the pathogen due to immunosuppression may also protect against the organ destroying cytokine storm caused by SARS-COV-2 and lead to a favourable outcome 32,33 . But the study of Minotti et al included mostly children or adults with rare immunodeficiencies in contrast to our cohort 33 4,28,30,31 . But they reported smaller case series and all patients had the same underlying disease.…”
Section: Discussionmentioning
confidence: 81%
“…As the mortality rate is higher in patients who are receiving immunosuppressive drugs, therefore calcineurin inhibitor and antimetabolite withdrawal or dose decreasing are recommended for COVID-19 patients [65].…”
Section: Histopathological Changesmentioning
confidence: 99%
“…Firstly, due to the chronic immunosuppressive therapy and ensuing suppression of cellular immunity, this population is at higher risk of viral infections [5]. Secondly, chronic immunosuppressive therapy has various immunomodulatory effects and could impair with the immunologic response during COVID-19 [5,[13][14][15]. Furthermore, frailty and susceptibility for recurrent kidney impairments during any infection portends these patients to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, frailty and susceptibility for recurrent kidney impairments during any infection portends these patients to adverse events. Increased cardiovascular risk, anemia, fluid imbalance, electrolyte disorders, and other companions of CKD could additionally impact the prognosis of these patients [14].…”
Section: Introductionmentioning
confidence: 99%